Effect of ventilator care bundle for pediatric nurses on occurrence of ventilator-associated pneumonia among children - Hanaa Diab Khalfallah; Nahed Alquwez; Marwa Abd Elkreem Ibrahim (BMC Nursing)
Abstract Background In pediatric intensive care units (PICUs), ventilator-associated pneumonia (VAP) is one of the most prevalent infections linked to healthcare. VAP affects 10% of children on mechanical ventilation (MV) and is associated with severe morbidity and mortality. The study aimed to evaluate the effect of the ventilator care bundle (VCB) on the occurrence of VAP among pediatric patients. Method A quasi-experimental design was conducted at Cairo University Specialized Pediatric Hospital (CUSPH), including all children who had mechanical ventilation within 24 h. VAP rates were evaluated before and after the implementation of a comprehensive VCB, which included head-of-bed elevation to 30–45°, hand hygiene reinforcement, sterile suctioning and handling of respiratory equipment, daily evaluation of extubation readiness, peptic ulcer prophylaxis, and deep venous thrombosis prophylaxis. A convenience sample of 30 nurses and a purposive sample of 60 ventilated children in the PICU participated in the study. Data collection was performed using (1) structured interview sheets, (2) the Nurses’ Knowledge Assessment Questionnaire (pre/post-test), (3) the Ventilator Bundle Checklist, and (4) the Clinical Pulmonary Infection Scale (CPIS). Results There was a significant increase in nurses’ level of knowledge before and after the implementation of the VCB (X² = 21.46, p ≤ 0.01). There was a statistically significant difference between the total mean scores of nurses’ practices in the first and second checklist readings (p < 0.01). Additionally, there were statistically significant differences between children in the study and control groups regarding the clinical pulmonary infection score (p < 0.01). The total mean score on the CPIS was significantly different between the study group and the control group (t = − 3.692, p = 0.001). Conclusion The study concluded that children who were cared for by nurses receiving VCB sessions were less likely to experience VAP compared to those in the control group. Recommendation Educational programs and in-service training courses for pediatric nurses to improve the quality of ventilator care for children and reduce the occurrence of VAP are essential.